2018
DOI: 10.1002/pd.5353
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and counseling challenges in prenatal exome sequencing

Abstract: Our study illustrates several challenges identified in an ongoing prenatal exome study. While genomic medicine is a powerful tool for prenatal diagnosis, it is important that clinicians understand the ethical implications and parental perceptions of this testing modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Additional research is needed on patient perspectives of the consent process, effective and appropriate communication of uncertainty, return of results and reinterpretation, and health and economic outcomes. 29 Publisher's note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research is needed on patient perspectives of the consent process, effective and appropriate communication of uncertainty, return of results and reinterpretation, and health and economic outcomes. 29 Publisher's note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.…”
Section: Resultsmentioning
confidence: 99%
“…The option of including incidental and secondary findings must be clarified in pretest counseling. 29…”
Section: Education Of Health-care Professionalsmentioning
confidence: 99%
“…For variants located in genes which were reported to cause moderate to severe childhood onset disorders but not found to be related to phenotypes in fetus. 9 Kristin G recommended that these variants should be included in the returned results if found to be highly penetrant pathogenic. Since many fetal disorders, including nonsyndromic intellectual disability, neurodevelopmental disorders, and metabolic disorder, cannot be diagnosed by fetal imaging, adequate pretest and post-test counseling are therefore supplemented as a commonly acknowledged practice in this area.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, previous studies have reported many challenges regarding the clinical application of WES in prenatal care, besides prenatal phenotyping limitations and technical problems, the counseling was also challenged with incidental or secondary findings, as well as variants of uncertain significance. 9,10 Meanwhile, it was suggested that diagnostic yields were higher in multiple fetal anomalies. 10 However, the observations of most CAKUT by prenatal sonography were isolated and sporadic, which suggests that genetic origin that potentially contributes to this cohort should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential complexities associated with exome sequencing, particularly in the prenatal period, it is not surprising that researchers are exploring parental experiences to identify issues that will need to be addressed when implementing clinically. One study confirmed the range of challenges that existed, including the need for adequate counseling and informed consent, prenatal variant interpretation, inability to identify a genetic aetiology, and identifying secondary findings in the parents when offering trio testing . The other study clearly showed that parents wanted as much information as possible, including uncertain results that might be related to the diagnosis .…”
Section: Introductionmentioning
confidence: 83%